PENGARUH PERGANTIAN MANAGEMEN, UKURAN KAP, PERTUMBUHAN PERUSAHAAN DAN OPINI AUDIT TERHADAP VOLUNTARY AUDITOR SWITCHING - Cynthia Angsana; Michael Michael; Selvia Selvia; Yenny Yenny; Wilsa Road Betterment Sitepu; Rika Dinarianti (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
The purpose of this study was to examine and analyze the effect of Management Change, KAP Size, Company Growth and Audit Opinion on Voluntary Auditor Switching in Basic and Chemical Industry Subsector Manufacturing Companies listed on the Indonesia Stock Exchange in 2013-2017. The research method used is a quantitative approach, with the nature of this research is cause and effect (causal). The population used in this study is 76 companies and there were 48 companies for the sample with the determination of the sample using a purposive sampling technique. The results of this research are partially influential and significant between Management Substitution, The size of the KAP, and Audit opinion towards Voluntary Auditor Switching. But, The Company's growth partially has no effect on Voluntary Auditor Switching. Management Change, KAP Size, Company Growth, and Audit Opinion simultaneously have a significant and significant effect on Voluntary Auditor Switching in the basic and chemical industry sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017.